Analysis of Merit System in the Open Promotion of High Leadership Positions for Women in the Ministry of Home Affairs - Tian Nirwana; Eko Prasojo (Journal of Governance and Public Policy, 2021)
This research aims to analyze the application of the merit system in the open promotion of High Leadership Positions (JPT) for women and find out the factors that influence women's vertical mobility in the bureaucracy. This research was conducted at the Ministry of Home Affairs using a postpositivist research approach and qualitative data collection technique. The results showed that filling in the JPT at the Ministry of Home Affairs has not been based on a succession plan, and there is a Pelaksana Tugas (Plt) JPT with a term exceeding the applicable provisions. In addition, there were differences in administrative requirements for selection vacancies with relevant regulations. The track record tracking process was only carried out through curriculum evaluation and monitoring and evaluation of High-ranking Officials (PPT) performance appraisals only based on Employee Performance Target (SKP) every year. Women's interest in registering for selection tends to be slight, and incomplete facilities support women's productivity. The results also showed differences from previous research. The merit system policy in this study refers to the Regulation of the Minister of Administrative Reform and Bureaucratic Reform (Permenpanrb) Number 15 of 2019. Besides, it also proves the inaccuracy of The Theory of Organizational Barries, Self-imposed Barriers, and Gender Role Congruity.